Review on a novel biosilica source for production of advanced silica-based materials: Wheat husk - Terzioğlu, Pınar; Yucel, Sevil; Kus, Cigdem (Wiley, 2019)
The growing cognizance of environmental matters elucidates the increasing attention thought the evaluation of bio-based by-products and waste materials in various applications. The agricultural-based industry results in considerable amounts of residues containing silica. In the past decade, extensive research studies had been executed to evaluate agricultural waste materials such as rice husk and rice straw. The results of the studies point out the possibility of evaluating such wastes to produce silica-based materials. Wheat husk is such an abundantly available waste obtained from the wheat milling process. It is containing noncrystalline silica, and thus, it can also be evaluated to produce value added materials. This study presents a comprehensive overview of the researches carried out on the properties and utilization of wheat husk as a silica source. The summary and discussion presented in this review would provide knowledge on wheat husk that is convenient to be utilized for the low-cost and sustainable production of silica-based materials such as aerogel, metal silicates, zeolite, silica-based ceramics, and composites.
Keywords: aerogel; agricultural waste; nanosilica; Triticum aestivum L; wheat hull